Analisis Hadist “Manajemen Waktu” - Muhammad Fauzan; Zainarti Zainarti (Pusat Riset dan Inovasi Nasional, 2025)
Time is one of the greatest blessings given by Allah SWT to humans and has an important role in the life of a Muslim. This article analyzes the hadith of Rasulullah SAW which says, “Take advantage of five things before five things,” which teaches the importance of time management in various aspects of life. This hadith emphasizes the use of youth, health, wealth, free time and life before the arrival of a more challenging phase. By understanding this hadith, Muslims are invited to manage their time productively, not only for worldly interests, but also to achieve spiritual blessings. This article also provides a guide to the practical implementation of time management according to Islamic teachings.